Tinjauan Literatur Terhadap Media Pembelajaran Berbasis E-book Interaktif dalam Pembelajaran IPA - Maulida, Qonita; Lifti Rosyida, Zulfiana; Ainun Jariyah, Ita (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This study aims to review the literature related to the use of interactive e-book-based learning media in learning Science in Junior High School (SMP). By utilizing multimedia elements, such as animation, video and interactive quizzes, interactive e-books offer an innovative approach in helping students understand complex scientific concepts. This research uses the literature study method by reviewing various articles and relevant research. The results showed that interactive e-books can increase learning motivation, concept understanding, and student engagement. However, the implementation of interactive e-books still faces challenges, such as limited technological infrastructure, lack of teacher technical skills, and accessibility barriers. Therefore, careful planning and teacher training are needed to ensure the effectiveness of using interactive e-books in science learning.